Effect of steel fibres extracted from recycled tyres on plastic shrinkage cracking in self-compacting concrete. Issue 24 (21st December 2021) - Sayahi, Faez; Emborg, Mats; Hedlund, Hans; Cwirzen, Andrzej
Abstract : This paper investigates and compares the effect of steel fibres obtained through recycling waste tyres (known as RTSF), and a commercially available hooked steel fibre (HSF), on plastic shrinkage cracking in self-compacting concrete. The volumetric deformations of the specimens, bleeding, and the mass loss have been quantified. Mixtures containing 2.5, 5, 7.5 and 10 kg/m 3 of RTSF, and 5 and 7.5 kg/m 3 of HSF have been tested. The results show that an almost similar reduction of the crack area can be attained if HSF is replaced by a slightly higher amount of RTSF. However, the former seems to be more effective in restraining plastic shrinkage. Both fibres decreased the volumetric shrinkage and the bleeding capacity of the specimens.